Toward a conceptualization of perceived complaint handling quality in social media and traditional service channels. (14th May 2018) - Sugathan, Praveen; Rossmann, Alexander; Ranjan, Kumar Rakesh
Abstract : Purpose: This study aims to conceptualize and test the effect of consumers' perceptions of complaint handling quality (PCHQ) in both traditional and social media channels. Design/methodology/approach: Study 1 systematically reviews the relevant literature and then carries out a consumer and manager survey. This approach aims to conceptualize the dimensionality of PCHQ. Study 2 tests the effect of PCHQ on key marketing outcomes. Using survey data from a German telecommunications company, the study provides an explanation for the differences in outcomes across traditional (hotline) and social media channels. Findings: Study 1 reveals that PCHQ is best conceptualized as a five-dimensional construct with 15 facets. There are significant differences between customers and managers in terms of the importance attached to the various dimensions. The construct shows strong psychometric properties with high reliability and validity, thereby opening up opportunities to treat these facets as measurement indicators for the construct. Study 2 indicates that the effect of PCHQ on consumer loyalty and word-of-mouth (WOM) communication is stronger in social media than in traditional channels. Procedural justice and the overall quality of service solutions emerge as general dimensions of PCHQ because they are equally important in both channels. In contrast, interactional justice, distributive justice and customer effort have varying effects across the two channels. Research limitations/implications: This study contributes to the understanding of a firm's channel selection for complaint handling in two ways. First, it evaluates and conceptualizes the PCHQ construct. Second, it compares the effects of different dimensions of PCHQ on key marketing outcomes across traditional and social media channels. Practical implications: This study enables managers to understand the difference in efficacy attached to different dimensions of PCHQ. It further highlights such differences across traditional and social media service channels. For example, the effect of complaint handling on social media is of particular importance when generating WOM communication. Originality/value: This study offers a comprehensive conceptualization of the PCHQ construct and reveals the general and channel contingent effects of its different dimensions on key marketing outcomes.